Implementing constructivist approach into online course designs in Distance Education Institute at Eastern Mediterranean University - Altinay, Zehra (My University, 2009)
Change and development in work settings for better working practice through projects has become essential. And, in this context, learning through working practice is constructed by participatory action research. This work-based research has a significant role to contribute innovative practice of Distance Education Institute at Eastern Mediterranean University by EUA norms. The research aimed to investigate implementing constructivist approach into online course designs to develop learning and skills of the online students based on teamwork inspiration within the institute. Action research approach employed in this qualitative research in order to provide insights on how to prepare and design online courses based on constructivist approach. Training, in-depth interviews, documentary analysis, focus group, research diary and semi-structured interviews were employed as data collection techniques to gather large amount of data from online tutors, and members of institute in relation to their collaborative efforts within the process. Furthermore, triangulated data were analyzed based on content analysis in this inductive journey. The results revealed that members and the tutors had no prior knowledge and experience on team work culture and the principles of constructivist approach into online course designs. In this respect, collaborative efforts and synergy power of the tutors within participatory action research resulted in better working performance for change and development research actions. This research is significant for considering change and development in working practice in relation to implementing constructivist approach into online course designs as it is one of the critical success factor for the quality in online practices. In addition, the research opens an academic debate which work based projects through participatory action research need to function in working practices to propose change and development for the quality improvements within higher education institutions. © The Turkish Online Journal of Educational Technology 2002.
Keywords: Constructivism; Course design; Online education; Work based project